Genome-wide landscape of ApiAP2 transcription factors reveals a heterochromatin-associated regulatory network during Plasmodium falciparum blood-stage development. Issue 6 (14th March 2022) - Shang, Xiaomin; Wang, Changhong; Fan, Yanting; Guo, Gangqiang; Wang, Fei; Zhao, Yuemeng; Sheng, Fei; Tang, Jianxia; He, Xiaoqin; Yu, Xinyu; Zhang, Meihua; Zhu, Guoding; et al.
Abstract: Heterochromatin-associated gene silencing controls multiple physiological processes in malaria parasites, however, little is known concerning the regulatory network and cis -acting sequences involved in the organization of heterochromatin and how they modulate heterochromatic gene expression. Based on systematic profiling of genome-wide occupancy of eighteen Apicomplexan AP2 transcription factors by ChIP-seq analysis, we identify and characterize eight heterochromatin-associated factors (PfAP2-HFs), which exhibit preferential enrichment within heterochromatic regions but with differential coverage profiles. Although these ApiAP2s target euchromatic gene loci via specific DNA motifs, they are likely integral components of heterochromatin independent of DNA motif recognition. Systematic knockout screenings of ApiAP2 factors coupled with RNA-seq transcriptomic profiling revealed three activators and three repressors of heterochromatic gene expression including four PfAP2-HFs. Notably, expression of virulence genes is either completely silenced or significantly reduced upon the depletion of PfAP2-HC. Integrated multi-omics analyses reveal autoregulation and feed-forward loops to be common features of the ApiAP2 regulatory network, in addition to the occurrence of dynamic interplay between local chromatin structure and ApiAP2s in transcriptional control. Collectively, this study provides a valuable resource describing the genome-wide landscape of the ApiAP2 family and insights into functional divergence and cooperation within this family during the blood-stage development of malaria parasites.